2011
DOI: 10.1016/j.jnucmat.2011.01.077
|View full text |Cite
|
Sign up to set email alerts
|

La2O3-reinforced W and W–V alloys produced by hot isostatic pressing

Abstract: W and W V alloys reinforced with La 2 O 3 particles have been produced by MA and subsequent HIP at 1573 K and 195 MPa. The microstructure of the consolidated alloys has been characterized by scanning electron microscopy, energy dispersive spectroscopy analyses and X ray diffraction. The mechanical properties were studied by nanoindentation measurements. The results show that practically full dense billets of W V, W V La 2 O 3 and W La 2 O 3 alloys can be produced. The microstructure analysis has shown that isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Nevertheless, the DBTT and RCT for W can be improved by addition of some dopants. Recently, W 1Y 2 O 3 and W 1La 2 O 3 alloys have been produced by mechanical alloy ing and subsequent consolidation by hot isostatic pressing [4,5]. The improvement of the high temperature mechanical properties of the oxide dispersion strengthened (ODS) W alloys would be associated with the fine dispersion of the oxide nano particles, which can inhibit the dislocation motion and grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the DBTT and RCT for W can be improved by addition of some dopants. Recently, W 1Y 2 O 3 and W 1La 2 O 3 alloys have been produced by mechanical alloy ing and subsequent consolidation by hot isostatic pressing [4,5]. The improvement of the high temperature mechanical properties of the oxide dispersion strengthened (ODS) W alloys would be associated with the fine dispersion of the oxide nano particles, which can inhibit the dislocation motion and grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…The average crystallite size and cumulative microstrain estimated from the width of the XRD peaks were: 129.6 nm and 0.39% for 10 h milled W-4VLa, 29.0 nm and 0.56% for 20 h milled W-4TiLa, and 26.8 nm and 0.90% for 30 h milled W-4TiLa. The O excess in the milled powder rose significantly increasing the milling time from 10 to 30 h. SEM analyses revealed that the HIP treatment produced the segregation of some V or Ti into large pools of these elements sparsely distributed in the corresponding alloy [6,7]. Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Oxide reinforcement, or Al-K-Si doping, can enhance the mechanical strength of W and increase its recrystallization temperature, although without lowering the DBTT [3,4]. Recently, W-Ti and W-V alloys, reinforced or oxide dispersion strengthened (ODS) with Y 2 O 3 or La 2 O 3 , have been produced by mechanical alloying and subsequent consolidation by hot isostatic pressing (HIP) [5][6][7]. It has been reported that the addition of Ti by itself, or combined with Y 2 O 3 , can moderately enhance the strength and fracture toughness of W in the temperature range below 873 or 1073 K, and noticeably enhance microhardness [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…W-2V and ODS W-2V-0.5Y 2 O 3 (wt%) alloys, hereafter referred to as W2V and W2V0.5Y, were produced following a powder metallurgy route consisting of mechanical alloying and subsequent high isostatic pressing (HIP) for 2 h at 1573 K and 200 MPa, following the procedure described elsewhere [8].…”
Section: Methodsmentioning
confidence: 99%